Copper(II) Extraction from Nitric Acid Solution with 1-Phenyl-3-methyl-4-benzoyl-5-pyrazolone as a Cation Carrier by Liquid Membrane Emulsion - Baharuddin Hamzah; Noor Jalaluddin; Abdul Wahid Wahab; Ambo Upe (E-Journal of Chemistry)
Copper(II) extraction from nitric acid solution with 1-phenyl-3-methyl-4-benzoil-5-pyrazolone (HPMBP) as a cation carrier by liquid membrane emulsion (LME) was investigated. The HPMBP initially was synthesized and the synthesis yield is a yellow crystal with melting point of 87-89 °C. The synthesis efficiency is 72.04% and generally the spectra of IR, 1H NMR and 13C NMR agree with HPMBP structure. The optimum condition for copper(II) extraction were found as follows: concentration of mixed surfactant (span 80+span 20) was 3%, volume ratio of membrane and internal phase was 1, concentration of HPMBP was 0.020 M, concentration of HCl was 1 M, volume ratio of emulsion and external phase was 0.143. By using these optimum conditions, 30 mL of LME can extract 1000 ppm of copper(II) within 210 mL of nitric acid solution with extraction percentage of 97.97%.